Active tyrosine phenol-lyase aggregates induced by terminally attached functional peptides in Escherichia coli. (1st August 2020) - Han, Hongmei; Zeng, Weizhu; Zhang, Guoqiang; Zhou, Jingwen
Abstract: The formation of inclusion bodies (IBs) without enzyme activity in bacterial research is generally undesirable. Researchers have attempted to recovery the enzyme activities of IBs, which are commonly known as active IBs. Tyrosine phenol-lyase (TPL) is an important enzyme that can convert pyruvate and phenol into 3, 4-dihydroxyphenyl-l -alanine (L-DOPA) and IBs of TPL can commonly occur. To induce the correct folding and recover the enzyme activity of the IBs, peptides, such as ELK16, DKL6, L6KD, ELP10, ELP20, L6K2, EAK16, 18A, and GFIL16, were fused to the carboxyl terminus of TPL. The results showed that aggregate particles of TPL-DKL6, TPL-ELP10, TPL-EAK16, TPL-18A, and TPL-GFIL16 improved the enzyme activity by 40.9%, 50.7%, 48.9%, 86.6%, and 97.9%, respectively. The peptides TPL-DKL6, TPL-EAK16, TPL-18A, and TPL-GFIL16 displayed significantly improved thermostability compared with TPL. L-DOPA titer of TPL-ELP10, TPL-EAK16, TPL-18A, and TPL-GFIL16, with cells reaching 37.8 g/L, 53.8 g/L, 37.5 g/L, and 29.1 g/L, had an improvement of 111%, 201%, 109%, and 63%, respectively. A higher activity and L-DOPA titer of the TPL-EAK16 could be valuable for its industrial application to biosynthesize L-DOPA.